"Fear of Loss" Causing Family Anxiety who Treats Children with Hospitalization in Hospitals - Heni Dwi Windarwati (Jurnal Ilmu Keperawatan Jiwa, 2020)
The anxiety of families who care for children with hospitalization is caused by various causes. This study aims to explore the causes of family anxiety who care for children with hospitalization. This research uses a descriptive approach. The measuring instrument used was a predisposition and precipitation questionnaire that was developed referring to the Stuart adaptation concept. The number of samples in this study was 64 children with a descriptive analysis method. The cause of predisposition to family anxiety who care for children with hospitalization is more derived from socio-cultural factors, namely low education, poor communication patterns, and rarely involved in activities. Whereas more precipitation factors were found from psychological and social aspects, namely children being cared for and afraid of losing.